A corporate strategic paper for Philip Morris Philippines, Inc. - Edan, Alma Nimfa S. (Animo Repository, 1998)
The Philippine cigarette industry is growing at a modest rate of 5.45% per annum and is dominated by three major players. These companies share 90% of the total market while the rest share the remaining 10%. The surge in demand for premium brands of products is due to the discriminating taste of Filipino smokers, the growing female adult market segment whose choice is nothing less than the best and the long-term potential increase in consumers purchasing power. The recent passing of the Comprehensive Tax Reform Program (CTRP) made favourable impact on the industry as it puts companies on level playing grounds. This created short-term opportunities, which can be maximized by companies in the process of formulating their strategy. Philip Morris global brands dominate the premium segment of the market in the Philippines. With the volume and profitability targets set by regional management, the company has to expand into other segments to establish its presence and increase its market share. The present strategies of Philip Morris are geared towards these objectives, targeting wider product scope and focusing efforts on distribution. The strengths of Philip Morris in terms of its financial capabilities and global support indicate tremendous potential for growth. In the long-term, Philip Morris is envisioned to operate in a fully integrated environment with world-class manufacturing facilities and highly synergized marketing and sales force. All for the vision of being the leading cigarette company in the Philippines.